Air-Stable Secondary Phosphine Oxides for Nickel-Catalyzed Cross-Couplings of Aryl Ethers by C–O Activation - Ghorai, Debasish; Loup, Joachim; Zanoni, Giuseppe; Ackermann, Lutz (Synlett, 2019)
Air- and moisture-stable secondary phosphine oxides (SPOs) enabled nickel-catalyzed Kumada–Corriu cross-couplings of various arylmethyl ethers at room temperature by challenging C–O activation.
Keywords: C–O activation; arylation; cross-coupling; secondary phosphine oxide; nickel